Constractor's perception on the abandoned project problem in Ipoh, Perak - Hamdan, Muhammad Firkrool (2023)
Construction is a complicated and dynamic industrial sector. Abandonment of project also keep on happening from time to time. Many factors from the Developers, Consultant Team and also Contractors can influence the issue to occur. Therefore, his study aims to identify the factors of abandoned project, to determine the effects of abandoned project and to recommend the strategies that can be implement to reduce the abandoned project problem. Questionnaire survey was used in this research to obtain the data. The scope of this research only focuses on the G7 contractor in lpoh, Perak. The respondents answered the questionnaire on a Likert Scale questions and their answers are analysed using SPSS Version 26.0. It was discovered that cashflow problem is the most critical factor that affect a project to be abandon. This shows the importance of financial management in order to manage a project successfully. According to the findings, vandalism on abandoned project building is the highest voted effect among the grade G7 contractor in lpoh, Perak.